Antiquity Revisited: A Discussion with Anthony Arthur Long - Long, Anthony Arthur; Vertzagia, Despina (Conatus - Journal of Philosophy, 2020)
A discussion on antiquity with Anthony A. Long, one of the most distinguished scholars in the field of ancient philosophy, would be engaging in any case. All the more so, since his two recently published works, Greek Models of Mind and Self (2015) and How to be Free: An Ancient Guide to the Stoic Life (2018), provide the opportunity to revisit key issues of ancient philosophy. The former is a lively and challenging work that starts with the Homeric notions of selfhood, and leads the reader all the way through classical and Hellenistic philosophical psychology; the latter is a profound analysis of the Stoic ethics that focuses in particular on its foundation and principles, followed by Long’s re-worked translation of Epictetus’ Encheiridion and carefully selected parts of his Discourses. Anthony Long kindly accepted the invitation to discuss several issues that are in the core of scholarly concern, sharing interpretations and thoughts that originate from his long acquaintance with the ancient literary tradition.